Kedudukan Pendidikan Kewarganegaraan Dalam Membangun Pendidikan Karakter Di Era Globalisasi - Hasanah, Uswatun; ., Mustika Kirana Putri; ., Azizah Tun Nafsiyah; ., Wiwin Wulandari; ., Ilham Ibnu Firdaus (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
This study aims to analyze the position of citizenship education in building character education in the era of globalization. The research was carried out at SDN Banyuanyar Kidul with data obtained from interviews and data collection through questionnaires. This research was conducted to analyze the suitability of learning civics education in thematic learning in order to create character education for students. The results of the study show that the position of citizenship education in building educational character plays an important role for students of SDN Banyuanyar Kidul.